2023
DOI: 10.1111/mec.17058
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsial pathogens drive microbiota assembly in Hyalomma marginatum and Rhipicephalus bursa ticks

Abstract: Most tick-borne pathogens (TBPs) are secondarily acquired by ticks during feeding on infected hosts, which imposes 'priority effect' constraints, as arrival order influences the establishment of new species in a microbial community. Here we tested whether once acquired, TBPs contribute to bacterial microbiota functioning by increasing community stability. For this, we used Hyalomma marginatum and Rhipicephalus bursa ticks collected from cattle in different locations of Corsica and combined 16S rRNA amplicon se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…These results are consistent with previous studies performed on H. marginatum in southern France which reported high infection rates; from 75% in individual ticks in H. marginatum collected around the French Mediterranean sea between 2016 and 2019 (Bernard et al 2024) to 100% of the pools of H. marginatum in Corsica (Grech-Angelini et al 2020). Such high infection rates observed in our study and many others (Maitre et al 2023; Bernard et al 2024) raise the question of the pathogenic status of this detected Rickettsia, since a high number of human patients suffering from rickettsiosis should be observed, but reported cases remain extremely rare and only imported cases have been reported in France to date. While Grech-Angelini et al (2020) suggested that human exposure to R. aeschlimannii infection in Corsica is high and human cases of tick-borne spotted fever acquired in Corsica could often be due to R. aeschlimannii , there is no information available for its vectorial competence based on experimental approaches, showing that this assumption must be nuanced.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…These results are consistent with previous studies performed on H. marginatum in southern France which reported high infection rates; from 75% in individual ticks in H. marginatum collected around the French Mediterranean sea between 2016 and 2019 (Bernard et al 2024) to 100% of the pools of H. marginatum in Corsica (Grech-Angelini et al 2020). Such high infection rates observed in our study and many others (Maitre et al 2023; Bernard et al 2024) raise the question of the pathogenic status of this detected Rickettsia, since a high number of human patients suffering from rickettsiosis should be observed, but reported cases remain extremely rare and only imported cases have been reported in France to date. While Grech-Angelini et al (2020) suggested that human exposure to R. aeschlimannii infection in Corsica is high and human cases of tick-borne spotted fever acquired in Corsica could often be due to R. aeschlimannii , there is no information available for its vectorial competence based on experimental approaches, showing that this assumption must be nuanced.…”
Section: Discussionsupporting
confidence: 49%
“…Indeed, the transovarian transmission of R. aeschlimannii in H. marginatum paired with its high infection rates both support this assumption (Parola, Paddock, and Raoult 2005;Azagi et al 2017). In the literature, such hypothesis have already been suggested for H. marginatum (Maitre et al 2023;Boularias et al 2021). Tick symbionts are typically classified as primary or secondary symbionts, depending on their role in the tick's survival.…”
Section: The Scheming Dynamics Of Rickettsia Aeschlimanniimentioning
confidence: 99%
“…bursa ticks, suggesting it acts as a community assembly driver (Maitre et al, 2023). Conversely, in R. microplus, infection by the protozoan Theileria sp.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal changes in the vector microbiome may affect the ability of pathogens to persist in vectors, transmit to hosts, and cause disease, as the transmission of vector-borne pathogens often involves complex interactions between pathogens and the microbiome (Abraham et al, 2017;Maitre et al, 2022Maitre et al, , 2023Narasimhan et al, 2014Narasimhan et al, , 2017. While the studies by Krawczyk et al (2022), and Lejal et al (2021) provided valuable insights into the dynamic nature of symbiont-microbiome interactions and the temporal dynamics of TBPs within questing ticks, it is essential to acknowledge a crucial limitation inherent to this sampling approach.…”
Section: Introductionmentioning
confidence: 99%
“…Network analysis is a powerful tool that allows researchers to investigate the complex interactions and associations between different microbial taxa within a community [ 8 , 9 ]. By constructing co-occurrence networks based on correlations between microbial abundances, researchers can gain insights into the structure, organization, and stability of the microbial community [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%